Method for continuous production of a bi-functional membrane electrode for water electrolysis and fuel cells
Patent Information
- Application Number
- CN202311275994.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-09-28
AI Technical Summary
针对质子交换膜,在现有领域中,常有采用芳基吡啶聚合物作为质子交换膜的高分子骨架,此种不含醚键的聚合物作为骨架,可以有效解决降解问题,并且其具有较好的成膜性、化学稳定性、热稳定性等优势,但是由于芳基吡啶聚合物官能团限制和浸渍磷酸后溶胀严重等因素的考虑,通常会考虑机械强度的因素而限制减少浸渍量,而且由于分子结构中固有的吸附位点有限,也会同样限制浸渍量,因此影响电导率及膜的机械强度,进而影响膜电极的电导率和机械强度
[0092]1、本发明催化层的制备方式采用多层分层制备,且每层均针对性采用了不同的原料并控制了担量,首先,在接触膜的表面喷涂掺杂微晶纤维素/PVDF/PTFE的阳极催化剂浆料1/阴极催化剂浆料4,即首先涂覆一个过渡层,微晶纤维素等可以提高膜的结晶度,提高膜和催化层的结合力与结构强度、提高膜和催化层的界面相容性;
Smart Images

Figure CN117254077B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a continuous preparation method of a dual-effect membrane electrode for water electrolysis and fuel cells, belonging to the field of fuel cell and water electrolysis membrane materials and membrane electrode materials. Background Technology
[0002] The membrane electrode assembly (MEA) is one of the core components of fuel cells and water electrolyzers, determining the overall performance, lifespan, and price of the cell / electrolyzer. As a core component, the MEA mainly consists of a proton exchange membrane (PEM) in the middle and catalyst layers on both sides. Therefore, the performance of the PEM and catalyst layers directly affects the MEA's performance. For PEMs, arylpyridine polymers are commonly used as the polymeric framework. This type of polymer, which does not contain ether bonds, effectively solves the degradation problem and has advantages such as good film-forming properties, chemical stability, and thermal stability. However, due to the functional group limitations of arylpyridine polymers and the severe swelling after impregnation with phosphoric acid, the impregnation amount is usually limited to consider mechanical strength. Furthermore, the inherent limited adsorption sites in the molecular structure also limit the impregnation amount, thus affecting the conductivity and mechanical strength of the membrane, and consequently, the conductivity and mechanical strength of the MEA.
[0003] Regarding the catalyst layer, in existing technologies, perfluorosulfonic acid resin is often used as a binder in the catalyst slurry to ensure the proton transport rate of the catalyst layer and the adhesion between the catalyst and the proton exchange membrane. However, this method does not consider the transport rate of both in low-humidity and high-temperature environments, nor the interfacial resistance between them, which affects the transport performance. During stack operation, insufficient hydrogen supply to the anode can cause the voltage of a single cell to drop below zero volts. This phenomenon leads to severe corrosion of the anode catalyst, resulting in a decrease in the output performance of the hydrogen fuel cell. Secondly, in terms of preparation methods, existing technologies often use a mixture of multiple materials to form a slurry before direct coating. This method is relatively simple, but it presents significant problems, especially in the continuous fabrication of membrane electrodes in large batches, regarding coating uniformity and the full realization of performance. Summary of the Invention
[0004] The purpose of this invention is to provide a continuous preparation method for dual-effect membrane electrodes for water electrolysis and fuel cells. First, an arylpyridine polymer without unstable end groups such as ether bonds is used, and the polymer is modified with imidazole-functionalized graphene oxide to obtain the ability to conduct OH- or protons, respectively. Proton exchange membranes or anion exchange membranes are then prepared in one step to obtain dual-effect exchange membranes, which effectively improve the acid-base chemical stability of the membrane while maintaining good acid-base retention. Second, dual-effect membrane electrode catalyst layers are coated on both sides of the dual-effect polymer membrane. In the catalyst slurry of the catalyst layer, on the one hand, the same stereochemical resin material as the dual-effect polymer membrane is used, which can effectively reduce interfacial resistance and assist the catalyst in conducting ions. On the other hand, for the anode and cathode catalyst slurries, a layered preparation and multi-layer stacking method is adopted, and each layer is composed of different materials to form different structures, thereby obtaining a multi-layer structure and thus obtaining higher water electrolysis or fuel cell performance.
[0005] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:
[0006] This invention provides a method for preparing a dual-effect membrane electrode for water electrolysis and fuel cells, comprising the following steps:
[0007] (1) Anode catalyst slurry 1, anode catalyst slurry 2, and anode catalyst slurry 3 are sequentially coated on one side of the double-effect exchange membrane; after drying, cathode catalyst slurry 4, cathode catalyst slurry 5, and cathode catalyst slurry 6 are sequentially coated on the other side of the double-effect exchange membrane, and after drying, a spare double-effect membrane electrode is formed.
[0008] (2) The prepared standby dual-effect membrane electrode is soaked in an alkaline solution and dried to obtain an anion exchange membrane electrode; the prepared standby dual-effect membrane electrode is soaked in an acidic solution and dried to obtain a proton exchange membrane electrode.
[0009] The dual-effect exchange membrane comprises quaternized arylpyridine polymer and imidazole-functionalized graphene oxide, which can adsorb OH- or protons.
[0010] The quaternized arylpyridine polymer is obtained by an affinity substitution reaction between an arylpyridine polymer and a haloalkane.
[0011] The imidazole-functionalized graphene oxide is obtained by attaching an imidazole group to the carboxyl group on graphene oxide.
[0012] The anode catalyst slurry 1 is prepared by thoroughly mixing catalyst 1, compound 1, quaternized arylpyridine polymer 1, imidazole functionalized graphene oxide 1, and alcohol diluent. Catalyst 1 is one or a combination of 10-70 wt% Pt / C and Pt black. Compound 1 is one or more of microcrystalline cellulose, PVDF, and PTFE.
[0013] The anode catalyst slurry 2 is prepared by thoroughly mixing catalyst 2, compound 2, quaternized arylpyridine polymer 2, imidazole functionalized graphene oxide 2, and an alcohol diluent. Catalyst 2 is 10-70 wt% Pt / C or one or a combination of two of Pt black. Compound 2 is one or a combination of Ru, Ir, Co, Ni, Ta, Re, Sn, Sb or their oxides.
[0014] The anode catalyst slurry 3 is prepared by thoroughly mixing catalyst 3, compound 3, quaternized arylpyridine polymer 3, imidazole functionalized graphene oxide 3, and alcohol diluent. Catalyst 3 is 10-70 wt% Pt / C and one or a combination of two of Pt black. Compound 3 is one or a combination of one or more of TiO2, MnO, MnO2, CeO2, and ZrO2.
[0015] The cathode catalyst slurry 4 is prepared by thoroughly mixing catalyst 4, compound 4, quaternized arylpyridine polymer 4, imidazole functionalized graphene oxide 4, and alcohol diluent. The catalyst 4 is one or a combination of two of iridium black, iridium oxide, 10-70wt% Pt / C, and Pt black. The compound 4 is one or more of microcrystalline cellulose, PVDF, and PTFE.
[0016] The cathode catalyst slurry 5 is prepared by thoroughly mixing catalyst 5, compound 5, quaternized arylpyridine polymer 5, imidazole functionalized graphene oxide 5, and an alcohol diluent; catalyst 5 is one or a combination of two of iridium black, iridium oxide, amorphous IrOx / Ru catalyst, 10-70wt% Pt / C, and Pt black; compound 5 is one or a combination of one or more of Ru, Ir, Co, Ni, Ta, Re, Sn, Sb, or their oxides.
[0017] The cathode catalyst slurry 6 is prepared by thoroughly mixing catalyst 6, compound 6, quaternized arylpyridine polymer 6, imidazole functionalized graphene oxide 6, and alcohol diluent. Catalyst 6 is one or a combination of two of the following: iridium black, iridium oxide, amorphous IrOx / Ru catalyst, 10-70wt% Pt / C, and Pt black. Compound 6 is one or a combination of one or more of TiO2, MnO, MnO2, CeO2, and ZrO2.
[0018] In the above technical solution, the method further utilizes a roll-to-roll coating production line, including a conveyor route for conveying the roll material. Along the conveying direction of the conveyor route, the production line sequentially includes a roll unwinding roller, an anode coating area, a cathode coating area, an alkaline immersion tank, an acid immersion tank, a final drying oven, and a finished product take-up roller. Along the conveying direction of the conveyor route, the anode coating area sequentially includes a first anode coating area, a second anode coating area, and a third anode coating area. The cathode coating area sequentially includes a first cathode coating area, a second cathode coating area, and a third cathode coating area. The spraying area includes a first heating platform, a second heating platform, and a third heating platform for the coil material in the first anode coating area, the second anode coating area, and the third anode spraying area, respectively. The first cathode coating area, the second cathode coating area, and the third cathode spraying area also include a first partition drying tunnel, a second partition drying tunnel, and a third partition drying tunnel for the coil material. The first anode coating area, the second anode coating area, the third anode spraying area, the first cathode coating area, the second cathode coating area, and the third cathode spraying area are all connected to six feeding systems.
[0019] The above technical solution further includes the following steps:
[0020] (1) The anode catalyst slurry 1 is placed in a feeding system that is connected to the first anode coating area;
[0021] The anode catalyst slurry 2 is placed in a feeding system that is connected to the second anode coating area;
[0022] The anode catalyst slurry 3 is placed in a feeding system that is connected to the third anode spraying zone;
[0023] (2) The cathode catalyst slurry 4 is placed in a feeding system that is connected to the first cathode coating area;
[0024] The cathode catalyst slurry 5 is placed in a feeding system that is connected to the second cathode coating area;
[0025] The cathode catalyst slurry 6 is placed in a feeding system that is connected to the third cathode spraying zone;
[0026] (3) After the dual-effect film is formed into a roll, it is stretched, wound, and installed on the conveyor route of the production line;
[0027] (4) Along the conveying direction of the double-effect exchange membrane, anodic catalyst slurry 1, anodic catalyst slurry 2, and anodic catalyst slurry 3 are sequentially coated on one side of the double-effect exchange membrane. At the same time as coating, the first heating platform, the second heating platform, and the third heating platform are heated simultaneously. Then, cathode catalyst slurry 4, cathode catalyst slurry 5, and cathode catalyst slurry 6 are sequentially coated on the other side of the double-effect exchange membrane. At the same time as coating, the first zone drying tunnel, the second zone drying tunnel, and the third zone drying tunnel are heated simultaneously to form a spare double-effect membrane electrode.
[0028] (5) The prepared standby dual-effect membrane electrode continues to be conveyed on the roll-to-roll coating production line. After being immersed in the alkaline solution soaking tank and dried in the general oven, it is wound on the finished product winding roller to form an anion exchange membrane electrode. In this state, the acid solution soaking tank is closed.
[0029] Alternatively, the prepared standby dual-effect membrane electrode continues to be conveyed on the roll-to-roll coating production line. After online immersion in the acid soaking tank and drying in the general oven, it is wound up on the finished product winding roller to form a proton exchange membrane electrode. In this state, the alkaline soaking tank is closed.
[0030] (6) Offline soaking: The obtained anion exchange membrane electrode is cut into the required size and immersed offline in an alkaline soaking tank. Finally, it is dried to obtain the finished anion exchange membrane electrode in the dual-effect membrane electrode; or the obtained proton exchange membrane electrode is cut into the required size and immersed offline in an acid soaking tank. Finally, it is dried to obtain the finished proton exchange membrane electrode in the dual-effect membrane electrode.
[0031] In the above technical solution, further, in the anode catalyst slurry 1: the catalyst 1 carrying capacity is 0.01-0.1 mg / cm2; the catalyst 1 content in the alcohol dilution solvent is 0.01-20 mg / mL; the mass ratio of catalyst 1, compound 1, quaternized arylpyridine polymer 1, and imidazole functionalized graphene oxide 1 is 1:(5-20):(5-10):(0.01-0.5);
[0032] In the anode catalyst slurry 2, the catalyst loading is 0.1-0.5 mg / cm³. 2 The content of catalyst 2 in alcohol dilution solvent is 0.1-30 mg / mL; the mass ratio of catalyst 2, compound 2, quaternized arylpyridine polymer 2, and imidazole functionalized graphene oxide 2 is 1:(0.1-3):(2-8):(0.2-5);
[0033] In the anode catalyst slurry 3, the catalyst loading is 0.1-1.5 mg / cm³. 2The content of catalyst 3 in alcohol dilution solvent is 1-40 mg / mL; the mass ratio of catalyst 3, compound 3, quaternized arylpyridine polymer 3, and imidazole functionalized graphene oxide 3 is 1:(5-20):(5-10):(0.1-0.5).
[0034] In the cathode catalyst slurry 4, the catalyst loading is 0.05-0.5 mg / cm³. 2 The content of catalyst 4 in alcohol dilution solvent is 0.01-40 mg / mL; the mass ratio of catalyst 4, compound 4, quaternized arylpyridine polymer 4, and imidazole functionalized graphene oxide 4 is 1:(5-20):(5-10):(0.01-0.5).
[0035] In the cathode catalyst slurry 5, the catalyst loading is 0.2-1.5 mg / cm³. 2 The content of catalyst 5 in alcohol dilution solvent is 0.1-50 mg / mL; the mass ratio of catalyst 5, compound 2, quaternized arylpyridine polymer 5, and imidazole functionalized graphene oxide 5 is 1:(0.1-5):(2-10):(0.2-10);
[0036] In the cathode catalyst slurry 6, the catalyst loading is 0.1-3 mg / cm³. 2 The content of catalyst 6 in alcohol dilution solvent is 1-80 mg / mL; the mass ratio of catalyst 6, compound 6, quaternized arylpyridine polymer 6, and imidazole functionalized graphene oxide 6 is 1:(5-20):(5-15):(0.1-2);
[0037] The alcohol diluents are all mixtures of deionized water and alcohol solvents, with a mass ratio of deionized water to alcohol of 1:0.1-20. The alcohols are one or more of ethanol, ethylene glycol, propanol, and isopropanol.
[0038] In the above technical solution, the preparation method of the dual-effect exchange membrane is further as follows:
[0039] A. Preparation of quaternized arylpyridine polymers:
[0040] A-1. Add 4-acetylpyridine and aryl hydrocarbons to dichloromethane solvent, add catalyst and protonating agent at low temperature, then return to room temperature, react for one time and then purify to obtain arylpyridine polymer;
[0041] The molar ratio of 4-acetylpyridine to aryl hydrocarbon is (1:1)-(1.6:1);
[0042] The molar ratio of the arylpyridine polymer to the haloalkane is (1:1)-(1:5);
[0043] The aryl hydrocarbon is present in dichloromethane at a concentration of 0.1-2 mol / L;
[0044] The molar ratio of 4-acetylpyridine to the catalyst is (1:5)-(1:10);
[0045] The molar ratio of 4-acetylpyridine to the protonating agent is (1:5)-(1:20);
[0046] The catalyst is selected from trifluoroacetic acid and trichloroacetic acid, and the protonating agent is selected from trifluoromethanesulfonic acid and trinitrobenzenesulfonic acid;
[0047] The low temperature is -20 to 5°C;
[0048] The reaction time is 2-72 hours.
[0049] The aryl hydrocarbon is selected from any one or more of the following structures:
[0050]
[0051] A-2. Dissolve the arylpyridine polymer from step A-1 in a high-boiling-point solvent, add a haloalkane and heat, react for two hours and then purify to obtain the quaternized arylpyridine polymer.
[0052] The high-boiling-point solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone;
[0053] The halogenated hydrocarbon is selected from one or more of iodomethane, bromoethane, bromobutane, and bromohexane; the heating temperature is 50-200℃;
[0054] The second reaction time is 2-100 hours;
[0055] The arylpyridine polymer has a concentration of 0.01-2 mol / L in a high-boiling-point solvent;
[0056] B. Synthesis of imidazole-functionalized graphene oxide:
[0057] Graphene oxide is heated and refluxed in an acylation reagent until the carboxyl group is completely converted to acyl chloride. After purification, acylated graphene oxide is obtained. Then, it is mixed with a solvent and an imidazole salt with an amino side chain and heated to react. Finally, after purification, the imidazole functionalized graphene oxide is obtained, which is to attach an imidazole group to the carboxyl group on the graphene oxide.
[0058] The acylation reagent is selected from thionyl chloride and oxalyl chloride;
[0059] The solvent is selected from one or more of tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide;
[0060] The mass ratio of the graphene oxide to the volume ratio of the acylation reagent is (1:10)-(1:50) g / ml;
[0061] The molar ratio of the acylated graphene oxide to the imidazole salt with amino groups on the side chain is (1:1)-(1:3);
[0062] The mass ratio of the acylated graphene oxide to the volume ratio of the solvent is (1:5)-(1:100) g / ml;
[0063] The heating temperature of the reflux heating is 70-100℃;
[0064] The reaction time for the heating reflux is 24-72 hours;
[0065] The heating temperature for the heating reaction is 60-130℃;
[0066] The reaction time for the heating reaction is 8-50 hours;
[0067] The imidazole salt with an amino group on its side chain is one of the following S1-S5 structures:
[0068]
[0069] C. Dissolve the quaternized arylpyridine polymer from step A) in a high-boiling-point solvent to form solution one. Disperse the imidazole-functionalized graphene oxide from step B) in a high-boiling-point solvent to form solution two. Mix solution one and solution two again to form a film-forming slurry. Cast the film-forming slurry into a film and dry it to obtain a dual-effect exchange membrane.
[0070] The high-boiling-point solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone;
[0071] The mass-to-volume ratio of the quaternized arylpyridine polymer to the high-boiling solvent is (1:5)-(1:100) g / ml;
[0072] The mass-to-volume ratio of the imidazole-functionalized graphene oxide to the high-boiling-point solvent is (1:20)-(1:200) g / ml;
[0073] The mass ratio of imidazole-functionalized graphene oxide to quaternized arylpyridine polymer is (1:1000)-(1:10);
[0074] The wet thickness of the dual-effect exchange membrane is 40-350 μm;
[0075] The drying process employs vacuum drying, with a vacuum drying temperature of 50-200℃.
[0076] In the above technical solution, the structural formula of the obtained quaternized arylpyridine polymer is shown in formula (I), and the structural formula of the imidazole functionalized graphene oxide obtained in step 1) is shown in formula (II).
[0077]
[0078] Wherein, Ar is selected from aryl groups; R1 is selected from H, methyl, ethyl, butyl, or hexyl;
[0079]
[0080] In equation (Ⅱ), R2 is one of the S1-S5 structures.
[0081] In the above technical solution, further, in step 4), the coating parameters of the anode catalyst slurry 1 are: coating thickness of 1-200 μm, coating speed of 1-10 m / min, and temperature of the first heating platform of 50-150℃; the coating parameters of the anode catalyst slurry 2 are: coating thickness of 1-150 μm, coating speed of 1-20 m / min, and temperature of the second heating platform of 40-120℃; the spraying parameters of the anode catalyst slurry 3 are: spraying thickness of 1-30 μm, spraying speed of 1-15 m / min, and temperature of the third heating platform of 60-180℃.
[0082] The coating thickness of cathode catalyst slurry 4 is 1-30 μm, the coating speed is 1-10 m / min, and the temperature of the first zone drying tunnel is 70-150℃; the coating parameters of cathode catalyst slurry 5 are: coating thickness 1-50 μm, coating speed 1-10 m / min, and the temperature of the second zone drying tunnel is 60-120℃; the spraying parameters of cathode catalyst slurry 6 are: spraying thickness 0.1-35 μm, spraying speed 1-10 m / min, wet thickness 1-30 μm, and the temperature of the third zone drying tunnel is 80-250℃.
[0083] In the above technical solution, the alkaline solution in step (5) is selected from one or more of NaOH, Na2CO3, NaHCO3, KOH, K2CO3, and KHCO3 solutions; the acid in the acidic solution is selected from one or more of sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, polyphosphoric acid, phosphotungstic acid, phosphomolybdic acid, silicotungstic acid, and silicotungstic acid.
[0084] The concentration of the alkaline solution is 0.1-10 mol / L;
[0085] The concentration of the acidic solution is 0.01-5 mol / L;
[0086] The soaking time is 12-100 hours;
[0087] The drying temperature is 25-80℃;
[0088] The drying temperature during online soaking is 60-250℃.
[0089] The present invention also provides a dual-effect membrane electrode for water electrolysis and fuel cells, which is prepared by the aforementioned preparation method.
[0090] Furthermore, in the above technical solution, the dual-effect membrane electrode is used as a membrane electrode in water electrolysis and fuel cells or applied in anhydrous systems and high-temperature proton exchange membrane fuel cells with an operating temperature of 120-200℃.
[0091] Compared with the prior art, the present invention has the following beneficial effects:
[0092] 1. The catalyst layer of the present invention is prepared by multi-layer layering, and each layer uses different raw materials and controls the amount of each layer. First, anode catalyst slurry 1 and cathode catalyst slurry 4 doped with microcrystalline cellulose / PVDF / PTFE are sprayed onto the surface of the contact membrane, that is, a transition layer is first coated. Microcrystalline cellulose and the like can improve the crystallinity of the membrane, improve the bonding force and structural strength between the membrane and the catalyst layer, and improve the interfacial compatibility between the membrane and the catalyst layer.
[0093] Secondly, on this basis, a proton / OH- conductive anode catalyst slurry 2 / cathode catalyst slurry 5 is coated. This layer contains compound 2 / compound 5, which has the ability to improve the anti-reverse polarity. The beneficial effects of the anti-reverse polarity catalyst layer 2 / catalyst layer 5 directly contacting the catalyst layer 1 / catalyst layer 4, which has a tighter bonding force with the membrane, are: (1) The role of the anti-reverse polarity material is: it can form a certain current in a short time in the presence of low gas, which can make up for the short-term current loss caused by insufficient gas supply in the normal catalyst, thereby avoiding electrode reversal. The anti-reverse polarity layer should shorten the distance between itself and the membrane as much as possible, which can reduce the impact of short-term current changes on the membrane, such as overheating and perforation. (2) Due to the presence of the transition layer, the solvent's dissolution / swelling damage to the membrane during coating slurry is reduced. (3) After coating the catalyst layer 2 / catalyst layer 5, the bonding force between the catalyst layer 1 / catalyst layer 4 and the membrane will be improved, and the bonding force between the membrane and the catalyst layer will be further improved with the increase of polymer content. (4) The components in the catalyst layer 2 / catalyst layer 5 are different from those in the catalyst layer 1 / catalyst layer 4. The reason why the invention does not use the method of directly mixing the anti-reverse polarization material into the slurry 1 or 4 is because the presence of the anti-reverse polarization material will affect the dissolution and dispersion ability of microcrystalline cellulose, etc., and will reduce the effect of bonding ability. Therefore, layer coating is better than mixed coating.
[0094] Finally, anode catalyst slurry 3 and cathode catalyst slurry 6 are coated, and compound 3 / compound 6 are added. This functional layer is used to retain water, improve chemical stability (resist free radical attack), and has a high catalyst content to play a catalytic role in the electrocatalytic reaction between the anode and cathode. The beneficial effects of coating after catalyst layer 2 / catalytic layer 5 are: (1) The anode and cathode gases first come into contact with the outermost layer. This layer not only contains a high catalyst load to participate in the reaction, but also contains materials for free radical attack, which can resist the attack of free radicals on the polymer film. Free radicals are eliminated by using free radical quenchers in places far away from the polymer film. This approach is better than directly coating the functional layer containing quenchers on the film. (2) This layer has a high catalyst load, so the coating thickness is usually thicker. Coating this layer on the outermost layer can minimize the damage to the film caused by solvents and the coating process. In summary, by coating the anode and cathode with three functional layers, different layers can play their respective roles in the most appropriate positions.
[0095] 2. During stack operation, insufficient hydrogen supply to the anode can cause the voltage of a single cell to drop below zero volts. This phenomenon leads to severe corrosion of the anode catalyst, resulting in a decrease in the output performance of the hydrogen fuel cell. However, by adding anti-reverse electrode material, the membrane electrode developed in this invention incorporates anti-reverse electrode material in a certain layer. This material can generate a certain current for a short time in the presence of low gas, compensating for the temporary current loss caused by insufficient gas supply to the normal catalyst. Therefore, it can effectively cope with insufficient hydrogen supply to the anode and effectively resist corrosion of the catalyst layer.
[0096] 3. The three catalytic layers serve different functions, adding functional layers and placing them in appropriate locations: Catalytic layers 1 and 4 are in contact with the membrane to improve the adhesion and strength between the membrane and the catalytic layers; catalytic layers 2 and 5 are located in the middle to enhance the anti-reverse polarity within the catalytic layers and provide a better three-phase interface, i.e., to be as close as possible to the polymer membrane. Furthermore, catalytic layers 3 and 6 are usually thicker due to their high catalyst loading. If more catalytic layers are already on the membrane before coating these layers, direct solvent contact with the membrane can be reduced, thus reducing swelling and homogeneous cracking.
[0097] 4. This invention addresses the layered and multi-layered preparation of the catalyst layer, employing specific coating parameters and varying heating temperatures for each coating step. The temperature of the anode catalyst slurry 1 / cathode catalyst slurry 4, relative to the contact membrane, can be relatively higher, approaching the glass transition temperature of cellulose or resin, which enhances adhesion to the membrane. The temperature of the anode catalyst slurry 2 / cathode catalyst slurry 5 is then slightly lower, which helps reduce membrane swelling and catalyst layer cracking caused by solvent evaporation during the coating process. The outermost catalyst layer requires rapid drying because it has a relatively high load, necessitating a higher temperature to reduce the likelihood of uniform cracking.
[0098] 5. In the coating process of the cathode catalyst slurry, the present invention adopts a heating platform to provide support for the coating process and to better control temperature changes. In the coating process of the anode catalyst slurry, considering that the heating platform may damage the already coated cathode catalyst layer by reheating, a drying tunnel is used to heat the anode catalyst layer and ensure the uniformity of continuous preparation.
[0099] 6. The stereochemical resin of this invention utilizes the synthesized quaternized arylpyridine polymer, which effectively reduces catalyst particle agglomeration and improves catalyst dispersibility. Furthermore, it facilitates the uniform dispersion of various solvent molecules and polymeric sub-conductors in the slurry. During the drying process in a drying oven, the evaporation of the solvent leaves behind uniformly dispersed pores, providing a more continuous three-phase reaction interface (catalyst active component, water, and polymeric sub-conductor) for the catalyst layer, while also providing ample channels for gas exhaust. Therefore, the addition of the quaternized arylpyridine polymer improves solution dispersibility and promotes the formation and stability of the three-phase reaction interface.
[0100] 7. The dual-effect membrane electrode catalytic layer proposed in this invention contains catalytic layers with different functions on both sides. The material of the catalytic layer not only serves as a good binder, but the anode catalytic layer is composed of an anti-reverse electrode material and the same stereochemical resin, graphene, and catalyst as the polymer membrane. The anti-reverse electrode material enhances the membrane electrode's ability to cope with complex intake environments during battery operation. The use of the same stereochemical resin as the polymer and imidazole-modified graphene effectively avoids interfacial resistance caused by material differences. Compared with perfluorosulfonic acid binders, it has higher conductivity and smoother ion conduction channels. The cathode catalytic layer uses a catalyst with free radical quenching function and also uses the same components as the stereochemical resin. This preparation method can produce a dual-effect membrane electrode with superior performance and achieve good battery / electrolyte performance in low-humidity environments.
[0101] 8. In this invention, the steric resin of both the polymer film and the catalyst layer in the dual-effect membrane electrode is an arylpyridine polymer modified with imidazole-functionalized graphene oxide without unstable end groups such as ether bonds. Simultaneously, the polymer possesses highly chemically stable nitrogen heterocyclic functional groups, which further enhance chemical stability through steric hindrance. Therefore, degradation of the polymer backbone and functional groups within the membrane can be effectively avoided, resulting in excellent chemical stability. Furthermore, since the imidazole groups have abundant electrons, they can neutralize the electron transfer from graphene oxide to the pyridine polymer, effectively preventing a reduction in the number of electrons transferred from graphene, which could lead to graphene shedding and decreased stability. Therefore, the dual-effect membrane electrode of this invention exhibits good film-forming properties and conductivity. Moreover, the dual-effect membrane electrode with high phosphoric acid adsorption capacity proposed in this invention (after adsorbing proton conductors such as phosphoric acid) possesses good proton conductivity and excellent antioxidant stability even without humidification. Therefore, it can effectively solve the problem of the amount of impregnation affecting conductivity and mechanical strength, and also effectively alleviate the problem of phosphoric acid loss.
[0102] 9. The unique structure of the dual-effect polymer exchange membrane of this invention can adsorb OH- or protons, thereby gaining the ability to conduct OH- or protons respectively. It can prepare a polymer membrane with dual functions, that is, by introducing different soaking solutions into the stack, anion exchange membrane and proton exchange membrane can be directly prepared. Furthermore, anion exchange membrane electrode and proton exchange membrane electrode can be directly prepared in one step, eliminating the need to disassemble the stack to replace the membrane electrode. This effectively achieves a "low-cost, high-efficiency, and non-destructive" preparation and operation mode. By flexibly switching acid and alkaline conditions, the function of fuel cells or electrolyzers can be performed more quickly, safely, and with high performance.
[0103] 10. Functionalized graphene oxide can overcome the limitation of the number of proton conductors adsorbed, not only providing a large number of active sites and improving conductivity, but also effectively avoiding problems such as increased membrane resistance caused by the addition of graphene after functionalization modification; it can also effectively increase the content of basic groups such as imidazole and increase the compatibility of graphene with polymers, so that graphene oxide inorganic materials can be added into the membrane in a timely manner, thereby obtaining better film-forming performance and conductivity. Attached Figure Description
[0104] Figure 1 This is a schematic diagram of the production line for preparing this dual-effect polymer membrane;
[0105] In the diagram: 1. Unwinding roll; 2. Anode coating area; 2-1. First anode coating area; 2-2. Second anode coating area; 2-3. Third anode spraying area; 2-4. First heating platform; 2-5. Second heating platform; 2-6. Third heating platform; 3. Cathodic coating area; 3-1. First cathodic coating area; 3-2. Second cathodic coating area; 3-3. Third cathodic spraying area; 3-4. First drying tunnel; 3-5. Second drying tunnel; 3-6. Third drying tunnel; 4. Alkali soaking tank; 5. Acid soaking tank; 6. Finished product winding roll; 7-1. First feeding system; 7-2. Second feeding system; 7-3. Third feeding system; 7-4. Fourth feeding system; 7-5. Fifth feeding system; 7-6. Sixth feeding system.
[0106] Figure 2 The membrane composition structure diagram in Example 1. Detailed Implementation
[0107] A roll-to-roll coating production line for preparing dual-effect film electrodes, applicable to the following embodiments and comparative examples, is disclosed. The production line mainly includes a feeding system, a coating system, a conveying system, and a PLC control system. The feeding system is composed of commonly used components in the art, such as storage tanks, discharge pumps, feeding pipes, and valves. The conveying system includes conveying electrical components, sensor assemblies, and drive roller assemblies. The conveying electrical components include servo motor sets, and the drive roller assemblies include unwinding rollers, steering rollers, tensioning rollers, adjusting rollers, and take-up rollers. The conveying route provides tensioning and winding of the roll material and enables its conveying. At the same time, the PLC system realizes intelligent logic control of the entire production line.
[0108] The production line of this invention specifically includes a conveying route for conveying the rolled material. Along the conveying direction of the route, the production line sequentially includes a rolled material unwinding roller, an anode coating area, a cathode coating area, an alkaline immersion tank, an acid immersion tank, and a finished product winding roller. Along the conveying direction of the route, the anode coating area sequentially includes a first anode coating area, a second anode coating area, and a third anode spraying area. The cathode coating area sequentially includes a first cathode coating area, a second cathode coating area, and a third cathode spraying area. The first anode coating area, the second anode coating area, and the third anode spraying area are respectively provided with a first heating platform, a second heating platform, and a third heating platform for acting on the rolled material. The first cathode coating area, the second cathode coating area, and the third cathode spraying area are each provided with a first partition drying tunnel, a second partition drying tunnel, and a third partition drying tunnel for acting on the rolled material. The first anode coating area, the second anode coating area, the third anode spraying area, the first cathode coating area, the second cathode coating area, and the third cathode spraying area are respectively connected to six feeding systems.
[0109] Example 1:
[0110] Preparation of quaternized polymers and imidazole-functionalized graphene oxide:
[0111] S1. Add 2 mol of biphenyl and 2 mol of 4-acetylpyridine to 20000 ml of dichloromethane and cool to 5 °C. Add 10 mol of trifluoroacetic acid dropwise, followed by 10 mol of trifluoromethanesulfonic acid. After the addition is complete, return to room temperature and react for 2 h. Pour the reaction solution into a methanol aqueous solution to precipitate a white solid. Wash the white solid with potassium carbonate solution at 50 °C, then wash with deionized water until neutral, and dry to obtain an arylpyridine polymer.
[0112] S2. Dissolve 1 mol of arylpyridine polymer in 100,000 ml of DMSO, add 1 mol of iodomethane, heat to 50 °C, and react for 100 h. Pour the reacted solution into a mixed solution of diethyl ether and isopropanol to precipitate a solid. Wash the solid once with deionized water, dry it, and obtain the quaternized arylpyridine polymer with the following structural formula: Figure 2 a.
[0113] S3. 1 mol of graphene oxide and 1000 ml of oxaloyl chloride were heated under reflux at 70 °C for 24 h to obtain acylated graphene oxide. 500 ml of N,N-dimethylformamide and 1 mol of 1-methyl-3-(3-aminopropyl)-3-chloroimidazolium were added, and the mixture was heated to 60 °C for 8 h. The reaction solution was centrifuged to obtain a black solid, which was washed with diethyl ether and dichloromethane, and then dried to obtain the imidazolium-functionalized graphene oxide, with the structural formula shown below. Figure 2 b.
[0114] Slurry preparation steps:
[0115] Preparation of anode catalyst slurry 1: 10g of 10wt% Pt / C (coating weight controlled at 0.1mg / cm³) was used. 2 50g microcrystalline cellulose, 50g quaternized arylpyridine polymer, 1g imidazole functionalized graphene oxide and 100mL water and ethanol mixed solvent (water and alcohol ratio 1:0.1) are thoroughly mixed and placed in a feeding system connected to the first anode coating area.
[0116] Preparation of anode catalyst slurry 2: 10g of 10wt% Pt black (coating weight controlled at 0.01mg / cm²) was used. 2 ), 1gRu, 20g quaternized arylpyridine polymer, 2g imidazole functionalized graphene oxide and 1000mL water and ethanol mixed solvent (water and alcohol ratio 1:0.1) are thoroughly mixed and placed in a feeding system connected to the second anode coating area;
[0117] Preparation of anode catalyst slurry 3: 10g of 10wt% Pt / C (coating weight controlled at 0.1mg / cm³) was used. 2), 50g TiO2, 50g quaternized arylpyridine polymer, 2g imidazole functionalized graphene oxide and 10000mL water and ethanol mixed solvent (water and alcohol ratio 1:0.1) are thoroughly mixed and placed in a feeding system connected to the third anode coating area;
[0118] Preparation of cathode catalyst slurry 4: 10g of iridium black (coating weight controlled at 0.05mg / cm²) 2 50g microcrystalline cellulose, 50g quaternized arylpyridine polymer, 0.1g imidazole functionalized graphene oxide and 10000mL water and isopropanol mixed solvent (water and alcohol ratio 1:0.1) are thoroughly mixed and placed in a feeding system connected to the first cathode coating area.
[0119] Preparation of cathode catalyst slurry 5: 10g of iridium black (coating weight controlled at 0.2mg / cm²) 2 ), 1g Ru, 50g quaternized arylpyridine polymer, 2g imidazole functionalized graphene oxide and 10000mL water and ethanol mixed solvent (water and alcohol ratio 1:0.1) are thoroughly mixed and placed in a feeding system connected to the second cathode coating area;
[0120] Preparation of cathode catalyst slurry 6: 10g of iridium black (coating weight controlled at 0.1mg / cm2), 50g of TiO2... 2 50g of quaternized arylpyridine polymer, 1g of imidazole-functionalized graphene oxide, and 10000mL of a mixed solvent of water and ethanol (water to alcohol ratio 1:0.1) were thoroughly mixed and placed in a feeding system connected to the third cathode coating area.
[0121] Steps for preparing a dual-effect exchange membrane:
[0122] 100g of quaternized arylpyridine polymer and 500ml of NMP were prepared as solution one; 100g of imidazole-functionalized graphene oxide and 2000ml of NMP were prepared as solution two. Solution one and solution two were mixed evenly again to form a film-forming slurry. The film was formed by casting and dried in a vacuum oven at 50℃ to obtain a double-effect exchange membrane with a wet thickness of 40μm.
[0123] Continuous fabrication of dual-effect exchange membrane electrodes:
[0124] The prepared double-effect exchange membrane is formed into a roll and then stretched and wound onto the conveyor route of the production line.
[0125] Along the conveying direction of the double-effect exchange membrane, anode catalyst slurry 1 is coated sequentially on one side of the double-effect exchange membrane at a coating speed of 1 m / min, with a thickness of 1 μm. During this process, the first heating platform heats the membrane simultaneously at a temperature of 30°C. Anode catalyst slurry 2 is then coated at a coating speed of 1 m / min, with a thickness of 1 μm. During this process, the second heating platform heats the membrane simultaneously at a temperature of 40°C. Finally, anode catalyst slurry 3 is sprayed at a spray flow rate of 1 m / min, with a spray thickness of 1 μm. During this process, the third heating platform heats the membrane simultaneously at a temperature of 60°C.
[0126] Next, cathode catalyst slurry 4 is coated sequentially on the other side of the double-effect exchange membrane at a coating speed of 1 m / min, with a thickness of 1 μm. At this time, the first zone drying tunnel is simultaneously heated at a temperature of 60°C. Cathode catalyst slurry 5 is then coated at a coating speed of 1 m / min, with a thickness of 1 μm. At this time, the second zone drying tunnel is simultaneously heated at a temperature of 60°C. Cathode catalyst slurry 6 is then sprayed at a spray flow rate of 1 m / min, with a spray thickness of 0.1 μm. At this time, the third zone drying tunnel is simultaneously heated at a temperature of 70°C. This completes the formation of the standby double-effect membrane electrode.
[0127] The spare dual-effect membrane electrode continues to be conveyed on the above production line, passing through an alkaline soaking tank containing 0.01 mol / L NaOH solution at a speed of 1 m / min for online immersion, and then dried at 25°C in the main oven. Finally, it can be wound up by the finished product winding roller to obtain the anion exchange membrane electrode roll. In this state, the acid soaking tank is closed. The obtained anion exchange membrane electrode roll is cut into the required size and immersed offline in an alkaline soaking tank of 0.1 mol / L NaOH for 12 hours. Finally, it is dried at 25°C to obtain the finished anion exchange membrane electrode in the dual-effect membrane electrode.
[0128] or:
[0129] The spare dual-effect membrane electrode continues to be conveyed on the above production line, passing through an online immersion tank containing 0.01 mol / L phosphoric acid solution at a speed of 1 m / min. After drying at 25°C in the main oven, it can finally be wound up by the finished product winding roller to obtain the proton exchange membrane electrode roll. In this state, the alkaline immersion tank is closed. The obtained proton exchange membrane electrode roll is cut into the required size and immersed offline in an acid immersion tank containing 10 mol / L phosphoric acid for 12 hours. Finally, it is dried at 25°C to obtain the finished proton exchange membrane electrode in the dual-effect membrane electrode.
[0130] Example 2
[0131] Preparation of quaternized polymers and imidazole-functionalized graphene oxide:
[0132] S1. Add 2 mol of p-terphenyl and 3.2 mol of 4-acetylpyridine to 1000 mL of dichloromethane and cool to -20 °C. Add 32 mol of trichloroacetic acid dropwise, followed by 64 mol of trinitrobenzenesulfonic acid. After the addition is complete, return to room temperature and react for 72 h. Pour the reaction solution into an aqueous methanol solution to precipitate a white solid. Wash the white solid with potassium carbonate solution at 50 °C, then wash with deionized water until neutral, and dry to obtain an arylpyridine polymer.
[0133] S2. Dissolve 1 mol of arylpyridine polymer in 500 ml of N-methylpyrrolidone, add 5 mol of bromoethane, heat to 200 °C, and react for 100 h. Pour the reacted solution into a mixed solution of diethyl ether and isopropanol to precipitate a solid. Wash the solid three times with deionized water and dry to obtain the quaternized arylpyridine polymer.
[0134] S3. 1 mol of graphene oxide and 5000 ml of oxalyl chloride were heated under reflux at 100 °C for 72 h to obtain acylated graphene oxide. 10000 ml of N,N-dimethylformamide and 3 mol of 1-methyl-3-(3-aminopropyl)-3-chloroimidazolium were added, and the mixture was heated to 130 °C for 50 h. The reaction solution was centrifuged to obtain a black solid, which was washed with diethyl ether and dichloromethane and then dried to obtain the imidazolium-functionalized graphene oxide.
[0135] Slurry preparation:
[0136] Preparation of anode catalyst slurry 1: 10g of 70wt% Pt black (coating load controlled at 0.5mg / cm2), 1000g of PTFE, 100g of quaternized arylpyridine polymer, 5g of imidazole functionalized graphene oxide and 2000mL of water and isopropanol mixed solvent (water and alcohol ratio 1:20) were thoroughly mixed and placed in a feeding system connected to the first anode coating area;
[0137] Preparation of anode catalyst slurry 2: 10g of 70wt% Pt / C (coating weight controlled at 0.1mg / cm²) was used. 2 ), 30g Ni, 80g quaternized arylpyridine polymer, 5g imidazole functionalized graphene oxide and 30000mL water and ethanol mixed solvent (water and alcohol ratio 1:20) are thoroughly mixed and placed in a feeding system connected to the second anode coating area;
[0138] Preparation of anode catalyst slurry 3: 10g of 70wt% Pt black (coating weight controlled at 1.5mg / cm²) was used. 2), 200g ZrO2, 100g quaternized arylpyridine polymer, 5g imidazole functionalized graphene oxide and 40000mL water and ethanol mixed solvent (water and alcohol ratio 1:20) were thoroughly mixed and placed in a feeding system connected to the third anode coating area;
[0139] Preparation of cathode catalyst slurry 4: 10g of iridium black (coating weight controlled at 0.5mg / cm²) 2 ), 200g microcrystalline cellulose, 100g quaternized arylpyridine polymer, 5g imidazole functionalized graphene oxide and 40000mL water and ethanol mixed solvent (water and alcohol ratio 1:20) are thoroughly mixed and placed in the feeding system connected to the fourth cathode coating area;
[0140] Preparation of cathode catalyst slurry 5: 10g of amorphous IrOx / Ru catalyst (coating weight controlled at 1.5mg / cm³) 2 ), 50g Sb, 100g quaternized arylpyridine polymer, 100g imidazole functionalized graphene oxide and 500,000mL water and ethanol mixed solvent (water and alcohol ratio 1:20) were thoroughly mixed and placed in the feeding system connected to the fifth cathode coating area;
[0141] Preparation of cathode catalyst slurry 6: 10g of iridium black (coating weight controlled at 3mg / cm²) 2 ), 200g TiO2, 150g quaternized arylpyridine polymer, 20g imidazole functionalized graphene oxide and 800,000mL water and ethanol mixed solvent (water and alcohol ratio 1:20) were thoroughly mixed and placed in the feeding system connected to the sixth cathode coating area;
[0142] Preparation of dual-effect exchange membranes:
[0143] Solution 1 was prepared by mixing 100g of quaternized arylpyridine polymer and 10000ml of N-methylpyrrolidone. Solution 2 was prepared by mixing 100g of imidazole-functionalized graphene oxide and 20000g of N-methylpyrrolidone. Solution 1 and Solution 2 were mixed uniformly again to form a film-forming slurry. The film was formed by casting and dried in a vacuum oven at 200℃ to obtain a double-effect exchange membrane with a wet thickness of 350μm.
[0144] Continuous fabrication of dual-effect exchange membrane electrodes:
[0145] The prepared double-effect exchange membrane is formed into a roll, stretched, wound, and installed on the conveyor route of the production line.
[0146] Along the conveying direction of the double-effect exchange membrane, anode catalyst slurry 1 is coated sequentially on one side of the double-effect exchange membrane at a coating speed of 10 m / min, with a thickness of 200 μm. During this process, the first heating platform heats the slurry simultaneously at a temperature of 90 °C. Anode catalyst slurry 2 is then coated at a coating speed of 20 m / min, with a thickness of 150 μm. During this process, the second heating platform heats the slurry simultaneously at a temperature of 120 °C. Finally, anode catalyst slurry 3 is sprayed at a spray flow rate of 15 m / min, with a spray thickness of 250 μm. During this process, the third heating platform heats the slurry simultaneously at a temperature of 150 °C.
[0147] Next, cathode catalyst slurry 4 is coated sequentially on the other side of the double-effect exchange membrane at a coating speed of 10 m / min, with a thickness of 30 μm. At this time, the first drying tunnel is simultaneously heated at a temperature of 150 °C. Cathode catalyst slurry 5 is then coated at a coating speed of 10 m / min, with a thickness of 50 μm. At this time, the second drying tunnel is simultaneously heated at a temperature of 200 °C. Cathode catalyst slurry 6 is then sprayed at a spray flow rate of 10 m / min, with a spray thickness of 30 μm. At this time, the third drying tunnel is simultaneously heated at a temperature of 200 °C. This completes the formation of the standby double-effect membrane electrode.
[0148] The spare dual-effect membrane electrode continues to be conveyed on the above production line, passing through an alkaline soaking tank containing 10 mol / L NaOH solution at a speed of 1 m / min for online immersion, and then dried at 25°C in the main oven. Finally, it can be wound up by the finished product winding roller to obtain the anion exchange membrane electrode roll. In this state, the acid soaking tank is closed. The obtained anion exchange membrane electrode roll is cut into the required size and immersed offline in an alkaline soaking tank of 10 mol / L NaOH for 100 h. Finally, it is dried at 80°C to obtain the finished anion exchange membrane electrode in the dual-effect membrane electrode.
[0149] or:
[0150] The spare dual-effect membrane electrode continues to be conveyed on the above production line, passing through an online immersion tank containing a 5 mol / L phosphoric acid solution at a speed of 1 m / min. After drying at 25°C in the main oven, it can finally be wound up by the finished product winding roller to obtain the proton exchange membrane electrode roll. In this state, the alkaline immersion tank is closed. The obtained proton exchange membrane electrode roll is cut into the required size and immersed offline in a 5 mol / L phosphoric acid solution immersion tank for 100 h. Finally, it is dried at 80°C to obtain the finished proton exchange membrane electrode in the dual-effect membrane electrode.
[0151] Example 3:
[0152] Preparation of quaternized polymers and imidazole-functionalized graphene oxide:
[0153] S1. Add 1 mol of p-terphenyl, 1 mol of m-terphenyl, and 26 mol of 4-acetylpyridine to 650 mL of dichloromethane and cool to 0 °C. Add 20.8 mol of trifluoroacetic acid dropwise, followed by 31.2 mol of trinitrobenzenesulfonic acid. After the addition is complete, return to room temperature and react for 10 h. Pour the reaction solution into a methanol aqueous solution to precipitate a white solid. Wash the white solid with potassium carbonate solution at 50 °C, then wash with deionized water until neutral, and dry to obtain an arylpyridine polymer.
[0154] S2. Dissolve 1 mol of arylpyridine polymer in 8500 ml of N,N-dimethylformamide, add 4 mol of bromohexane, heat to 120 °C, and react for 50 minutes. Pour the reacted solution into a mixed solution of diethyl ether and isopropanol to precipitate a solid. Wash the solid twice with deionized water, and dry to obtain the quaternized arylpyridine polymer.
[0155] S3. 1 mol of graphene oxide and 3000 ml of oxalyl chloride were heated under reflux at 80 °C for 30 h to obtain acylated graphene oxide. 5000 ml of N,N-dimethylformamide and 2 mol of 1-methyl-3-(3-aminopropyl)-3-chloroimidazolium were added, and the mixture was heated to 90 °C for 48 h. The reaction solution was centrifuged to obtain a black solid, which was washed with diethyl ether and dichloromethane and then dried to obtain the imidazolium-functionalized graphene oxide.
[0156] Slurry preparation:
[0157] Preparation of anode catalyst slurry 1: 10g of 50wt% Pt / C (coating load controlled at 0.3mg / cm2), 500g of PTFE, 800g of quaternized arylpyridine polymer, 3g of imidazole functionalized graphene oxide and 1000mL of water and isool mixed solvent (water and alcohol ratio 1:10) were thoroughly mixed and placed in a feeding system connected to the first anode coating area;
[0158] Preparation of anode catalyst slurry 2: 10g of 50wt% Pt / (coating weight controlled at 0.08mg / cm²) was used. 2 ), 20g RuO2, 50g quaternized arylpyridine polymer, 3g imidazole functionalized graphene oxide and 20000mL water and n-propanol mixed solvent (water and alcohol ratio 1:10) were thoroughly mixed and placed in a feeding system connected to the second anode coating area;
[0159] Preparation of anode catalyst slurry 3: 10g of 50wt% Pt / C (coating weight controlled at 1mg / cm³) was used. 2), 100g CeO2, 800g quaternized arylpyridine polymer, 3g imidazole functionalized graphene oxide and 30000mL water and n-propanol mixed solvent (water and alcohol ratio 1:10) are thoroughly mixed and placed in a feeding system connected to the third anode coating area;
[0160] Preparation of cathode catalyst slurry 4: 10g of iridium oxide (coating weight controlled at 0.4mg / cm²) was used. 2 ), 100g microcrystalline cellulose, 80g quaternized arylpyridine polymer, 4g imidazole functionalized graphene oxide and 20000mL water and ethanol mixed solvent (water and alcohol ratio 1:10) are thoroughly mixed and placed in the feeding system connected to the fourth cathode coating area;
[0161] Preparation of cathode catalyst slurry 5: 10g of amorphous IrOx / Ru catalyst (coating load controlled at 0.9mg / cm2), 40g of Ru, 70g of quaternized arylpyridine polymer, 50g of imidazole functionalized graphene oxide and 200000mL of water and ethanol mixed solvent (water and alcohol ratio 1:8) were thoroughly mixed and placed in a feeding system connected to the fifth cathode coating area;
[0162] Preparation of cathode catalyst slurry 6: 10g of iridium black (coating weight controlled at 2.5mg / cm²) 2 ), 100g CeO2, 100g quaternized arylpyridine polymer, 10g imidazole functionalized graphene oxide and 500,000mL water and ethanol mixed solvent (water and alcohol ratio 1:5) are thoroughly mixed and placed in the feeding system connected to the sixth cathode coating area;
[0163] Preparation of dual-effect exchange membranes:
[0164] 100g of quaternized arylpyridine polymer and 10000ml of NMP were prepared as solution one, and 100g of imidazole-functionalized graphene oxide and 10000ml of NMP were prepared as solution two. Solution one and solution two were mixed uniformly again to form a film-forming slurry. The film was formed by casting and dried in a vacuum oven at 125℃ to obtain a double-effect exchange membrane with a wet thickness of 200μm.
[0165] Continuous fabrication of dual-effect exchange membrane electrodes:
[0166] The prepared double-effect exchange membrane is formed into a roll, stretched, wound, and installed on the conveyor route of the production line.
[0167] Along the conveying direction of the double-effect exchange membrane, anode catalyst slurry 1 is coated sequentially on one side of the double-effect exchange membrane at a coating speed of 5 m / min, with a thickness of 100 μm. At this time, the first heating platform heats simultaneously at a temperature of 60 °C. Anode catalyst slurry 2 is coated at a coating speed of 10 m / min, with a thickness of 75 μm. At this time, the second heating platform heats simultaneously at a temperature of 80 °C. Anode catalyst slurry 3 is sprayed at a spray flow rate of 7 m / min, with a spray thickness of 150 μm. At this time, the third heating platform heats simultaneously at a temperature of 100 °C.
[0168] Next, cathode catalyst slurry 4 is coated sequentially on the other side of the double-effect exchange membrane at a coating speed of 5 m / min, with a thickness of 15 μm. At this time, the first drying tunnel is heated simultaneously at a temperature of 100℃. Cathode catalyst slurry 5 is coated at a coating speed of 5 m / min, with a thickness of 25 μm. At this time, the second drying tunnel is heated simultaneously at a temperature of 130℃. Cathode catalyst slurry 6 is sprayed at a spray flow rate of 5 m / min, with a spray thickness of 15 μm. At this time, the third drying tunnel is heated simultaneously at a temperature of 150℃. This completes the formation of the standby double-effect membrane electrode.
[0169] The spare dual-effect membrane electrode continues to be conveyed on the above production line, passing through an alkaline soaking tank containing 5 mol / L NaOH solution at a speed of 1 m / min for online immersion, and then dried at 25°C in the main oven. Finally, it can be wound up by the finished product winding roller to obtain the anion exchange membrane electrode roll. In this state, the acid soaking tank is in the closed state. The obtained anion exchange membrane electrode roll is cut into the required size and immersed offline in an alkaline soaking tank of 5 mol / L NaOH for 55 hours. Finally, it is dried at 60°C to obtain the finished anion exchange membrane electrode in the dual-effect membrane electrode.
[0170] or:
[0171] The spare dual-effect membrane electrode continues to be conveyed on the above production line, passing through an online immersion tank containing a 2.5 mol / L phosphoric acid solution at a speed of 1 m / min. After drying at 25°C in the main oven, it can finally be wound up by the finished product winding roller to obtain the proton exchange membrane electrode roll. In this state, the alkaline immersion tank is closed. The obtained proton exchange membrane electrode roll is cut to the required size and immersed offline in a 2.5 mol / L phosphoric acid solution immersion tank for 55 hours. Finally, it is dried at 60°C to obtain the finished proton exchange membrane electrode in the dual-effect membrane electrode.
[0172] Comparative Example 1
[0173] Perfluorosulfonic acid resin was used instead of quaternized arylpyridine polymer, and the amount and method of addition were the same as in Example 1.
[0174] The method for preparing the dual-effect exchange membrane and membrane electrode is the same as in Example 1.
[0175] Comparative Example 2: Adjustment order of different layers in the anode and cathode catalyst layers
[0176] The difference from Example 1 lies in the different anode and cathode catalyst layers.
[0177] Preparation of cathode and anode catalyst slurry:
[0178] Preparation of anode catalyst slurry 1: 10g of 10wt% Pt / C (coating weight controlled at 0.1mg / cm³) was used. 2 50g microcrystalline cellulose, 50g quaternized arylpyridine polymer, 1g imidazole functionalized graphene oxide and 100mL water and ethanol mixed solvent (water and alcohol ratio 1:0.1) are thoroughly mixed and placed in a feeding system connected to the first anode coating area.
[0179] Preparation of anode catalyst slurry 2: 10g of 10wt% Pt black (coating weight controlled at 0.01mg / cm²) was used. 2 ), 1gRu, 20g quaternized arylpyridine polymer, 2g imidazole functionalized graphene oxide and 1000mL water and ethanol mixed solvent (water and alcohol ratio 1:0.1) are thoroughly mixed and placed in a feeding system connected to the second anode coating area;
[0180] Preparation of anode catalyst slurry 3: 10g of 10wt% Pt / C (coating weight controlled at 0.1mg / cm³) was used. 2 ), 50g TiO2, 50g quaternized arylpyridine polymer, 2g imidazole functionalized graphene oxide and 10000mL water and ethanol mixed solvent (water and alcohol ratio 1:0.1) are thoroughly mixed and placed in a feeding system connected to the third anode coating area;
[0181] Preparation of cathode catalyst slurry 4: 10g of iridium black (coating weight controlled at 0.05mg / cm²) 2 50g microcrystalline cellulose, 50g quaternized arylpyridine polymer, 0.1g imidazole functionalized graphene oxide and 10000mL water and isopropanol mixed solvent (water and alcohol ratio 1:0.1) are thoroughly mixed and placed in a feeding system connected to the fourth cathode coating area.
[0182] Preparation of cathode catalyst slurry 5: 10g of iridium black (coating weight controlled at 0.2mg / cm²) 2), 1g Ru, 50g quaternized arylpyridine polymer, 2g imidazole functionalized graphene oxide and 10000mL water and ethanol mixed solvent (water and alcohol ratio 1:0.1) were thoroughly mixed and placed in the feeding system connected to the 5th cathode coating area;
[0183] Preparation of cathode catalyst slurry 6: 10g of iridium black (coating weight controlled at 0.1mg / cm²) 2 ), 50g TiO2, 50g quaternized arylpyridine polymer, 1g imidazole functionalized graphene oxide and 10000mL water and ethanol mixed solvent (water and alcohol ratio 1:0.1) were thoroughly mixed and placed in a feeding system connected to the sixth cathode coating area;
[0184] The catalyst slurry described above was used to prepare a double-effect exchange membrane and membrane electrode according to the method in Example 1.
[0185] Comparative Example 3
[0186] The difference from Example 1 lies in the temperature used when preparing the spare dual-effect film electrode.
[0187] A double-effect exchange membrane was prepared according to the method of Example 1. Along the conveying direction of the double-effect exchange membrane, anode catalyst slurry 1 was coated sequentially on one side of the double-effect exchange membrane at a coating speed of 1 m / min, with a thickness of 1 μm. At this time, the first heating platform was simultaneously heated at a heating temperature of 30°C. Anode catalyst slurry 2 was coated at a coating speed of 1 m / min, with a thickness of 1 μm. At this time, the second heating platform was simultaneously heated at a heating temperature of 60°C. Anode catalyst slurry 3 was sprayed at a spray flow rate of 1 m / min, with a spray thickness of 1 μm. At this time, the third heating platform was simultaneously heated at a heating temperature of 50°C.
[0188] Next, cathode catalyst slurry 4 is coated sequentially on the other side of the double-effect exchange membrane at a coating speed of 1 m / min, with a thickness of 1 μm. At this time, the first drying tunnel is heated simultaneously at a temperature of 30°C. Cathode catalyst slurry 5 is then coated at a coating speed of 1 m / min, with a thickness of 1 μm. At this time, the second drying tunnel is heated simultaneously at a temperature of 60°C. Cathode catalyst slurry 6 is then sprayed at a spray flow rate of 1 m / min, with a spray thickness of 0.1 μm. At this time, the third drying tunnel is heated simultaneously at a temperature of 50°C. This completes the formation of the standby double-effect membrane electrode.
[0189] The prepared dual-effect membrane electrode was immersed in an alkaline solution or an acid solution according to the method in Example 1 to obtain the finished membrane electrode.
[0190] Comparative Example 4
[0191] The difference from Example 1 lies in the heating steps used to prepare the spare dual-effect film electrode.
[0192] A double-effect exchange membrane was prepared according to the method in Example 1. Along the conveying direction of the double-effect exchange membrane, anode catalyst slurry 1 was coated sequentially on one side of the double-effect exchange membrane at a coating speed of 1 m / min, with a thickness of 1 μm; anode catalyst slurry 2 was coated at a coating speed of 1 m / min, with a thickness of 1 μm; and anode catalyst slurry 3 was sprayed at a spray flow rate of 1 m / min, with a spray thickness of 1 μm. The anode catalyst slurry was then dried and heated at a temperature of 100°C.
[0193] Then, cathode catalyst slurry 4 was coated on the other side of the double-effect exchange membrane at a coating speed of 1 m / min, with a thickness of 1 μm; cathode catalyst slurry 5 was coated at a coating speed of 1 m / min, with a thickness of 1 μm; cathode catalyst slurry 6 was sprayed at a spray flow rate of 1 m / min, with a spray thickness of 0.1 μm. The cathode catalyst slurry was then dried and heated at 100℃, thus forming a standby double-effect membrane electrode.
[0194] The prepared dual-effect membrane electrode was immersed in an alkaline solution or an acid solution according to the method in Example 1 to obtain the finished membrane electrode.
[0195] Comparative Example 5:
[0196] The difference from Example 1 is that the anode and cathode catalyst slurries are different.
[0197] Preparation of anode catalyst slurry: 10g of 10wt% Pt / C (coating weight controlled at 0.1mg / cm²) was used. 2 50g microcrystalline cellulose, 1g Ru, 50g TiO2, 50g quaternized arylpyridine polymer, 1g imidazole functionalized graphene oxide and 100mL water and ethanol mixed solvent (water and alcohol ratio 1:0.1) are thoroughly mixed and placed in a feeding system connected to the first anode coating area.
[0198] Preparation of cathode catalyst slurry: 10g of iridium black (coating weight controlled at 0.05mg / cm²) was used. 2 ), 1gRu, 50g microcrystalline cellulose, 50g TiO2, 50g quaternized arylpyridine polymer, 0.1g imidazole functionalized graphene oxide and 10000mL water and isopropanol mixed solvent (water and alcohol ratio 1:0.1) are thoroughly mixed and placed in a feeding system connected to the first cathode coating area;
[0199] A dual-effect exchange membrane was prepared according to the method in Example 1.
[0200] Along the conveying direction of the double-effect exchange membrane, the anode catalyst slurry is coated sequentially on one side of the double-effect exchange membrane at a coating speed of 1 m / min. The thickness of the anode catalyst slurry is 1 μm. At this time, the first heating platform is heated simultaneously at a heating temperature of 30℃.
[0201] Then, cathode catalyst slurry is coated on the other side of the double-effect exchange membrane at a coating speed of 1 m / min. The thickness of the cathode catalyst slurry is 1 μm. At this time, the first zone drying tunnel is heated simultaneously at a temperature of 60°C, thus forming a standby double-effect membrane electrode.
[0202] The prepared dual-effect membrane electrode was immersed in an alkaline solution or an acid solution according to the method in Example 1 to obtain the finished membrane electrode.
[0203] Comparative Example 6
[0204] Step 1) Preparation of anode catalyst slurry 1: 10g of 10wt% Pt / C (coating weight controlled at 0.1mg / cm³) 2 50g microcrystalline cellulose, 50g arylpyridine polymer, 1g graphene oxide and 100mL water and ethanol mixed solvent (water and alcohol ratio 1:0.1) are thoroughly mixed and placed in a feeding system connected to the first anode coating area;
[0205] Preparation of anode catalyst slurry 2: 10g of 10wt% Pt black (coating weight controlled at 0.01mg / cm²) was used. 2 ), 1gRu, 20g arylpyridine polymer, 2g graphene oxide and 1000mL water and ethanol mixed solvent (water and alcohol ratio 1:0.1) are thoroughly mixed and placed in a feeding system connected to the second anode coating area;
[0206] Preparation of anode catalyst slurry 3: 10g of 10wt% Pt / C (coating weight controlled at 0.1mg / cm³) was used. 2 ), 50g TiO2, 50g arylpyridine polymer, 2g graphene oxide and 10000mL water and ethanol mixed solvent (water and alcohol ratio 1:0.1) are thoroughly mixed and placed in a feeding system connected to the third anode coating area;
[0207] Step 2), Preparation of cathode catalyst slurry 4: 10g of iridium black (coating weight controlled at 0.05mg / cm²) 2 50g microcrystalline cellulose, 50g arylpyridine polymer, 0.1g graphene oxide and 10000mL water and isopropanol mixed solvent (water and alcohol ratio 1:0.1) are thoroughly mixed and placed in a feeding system connected to the first cathode coating area.
[0208] Preparation of cathode catalyst slurry 5: 10g of iridium black (coating weight controlled at 0.2mg / cm²) 2 ), 1g Ru, 50g arylpyridine polymer, 2g graphene oxide and 10000mL water and ethanol mixed solvent (water and alcohol ratio 1:0.1) are thoroughly mixed and placed in a feeding system connected to the second cathode coating area;
[0209] Preparation of cathode catalyst slurry 6: 10g of iridium black (coating weight controlled at 0.1mg / cm2), 50g of TiO2... 2 50g of arylpyridine polymer, 1g of graphene oxide and 10000mL of water and ethanol mixed solvent (water and alcohol ratio 1:0.1) were thoroughly mixed and placed in a feeding system connected to the third cathode coating area.
[0210] Step 3) Preparation of a dual-effect exchange membrane:
[0211] S2. Prepare solution one by mixing 100g of arylpyridine polymer and 500ml of NMP; prepare solution two by mixing 100g of graphene oxide and 2000ml of NMP. Mix solution one and solution two evenly again to form a film-forming slurry. Form a film by casting and dry it in a vacuum oven at 50℃ to obtain a double-effect exchange membrane with a wet thickness of 40μm.
[0212] The preparation of the arylpyridine polymer in steps 1), 2), and 3) is as follows: 2 mol of biphenyl and 2 mol of 4-acetylpyridine are added to 20000 ml of dichloromethane, and the mixture is cooled to 5°C. 10 mol of trifluoroacetic acid is added dropwise, followed by 10 mol of trifluoromethanesulfonic acid. After the addition is complete, the mixture is returned to room temperature and reacted for 2 hours. The resulting solution is poured into a methanol-water solution to precipitate a white solid. The white solid is washed with potassium carbonate solution at 50°C, then washed with deionized water until neutral, and dried to obtain the arylpyridine polymer.
[0213] The prepared dual-effect exchange membrane is formed into a roll and then stretched and wound onto the conveyor route of the production line; the anion exchange membrane electrode or the proton exchange membrane electrode is prepared according to the method of Example 1.
[0214] The acid-base retention rate, chemical stability, conductivity, tensile strength, dimensional change rate, and chemical stability of the dual-effect membrane electrodes prepared in the test examples and comparative examples were evaluated. The conductivity was tested at 120℃ and 40% humidity, and at 100℃ and 30% humidity. The tensile strength was tested using the national standard method (GB / T20042.3-2009). The hydrogen permeation current was tested using an electrochemical method.
[0215] Comparative Example 1: The catalyst slurry uses perfluorosulfonic acid resin instead of the stereochemical resin of the same material as the polymer membrane. Due to the interfacial resistance between the different materials, it hinders the conduction of OH- or protons and cannot form a good continuous transport channel, thus obtaining lower electrical conductivity and other properties.
[0216] In Comparative Example 2, the catalyst layer was not coated at the specific position of the present invention. The outermost layer of the anode and cathode of Example 1 was coated as the innermost layer, the middle layer of Example 1 was coated as the outermost layer, and the innermost layer of Example 1 was coated as the middle layer. Due to the change in the number of layers, the membrane electrode experienced uniform cracking during the coating process, and the mechanical strength and chemical stability also decreased accordingly. This is because the electrochemical performance of the original outermost layer was affected when it was placed in the inner layer, and the effects of the free radical quenching layer and the anti-reverse electrode layer were also reduced after the position was changed.
[0217] Comparative Example 3 shows that the drying temperature was set according to the slurry characteristics of the corresponding catalyst layer. It can be seen that due to improper temperature setting, the coating layer obtained in this comparative example will have problems such as uniform cracking. Moreover, the poor bonding force between the catalyst layer and the film results in a lower conductivity than that of the example.
[0218] In Comparative Example 4, the anode catalyst slurry and the cathode catalyst slurry were heated uniformly without distinction. During the preparation process, it was found that if the temperature was not limited or optimized, uniform cracking occurred when coating the outermost catalyst layer due to unsuitable temperature. In the inner layer coating process, the adhesion to the film decreased due to unsuitable temperature, which affected ion conduction.
[0219] Comparative Example 5: The anode catalyst slurry and cathode catalyst slurry were not prepared in layers, i.e., they were all mixed. Due to the different physical properties and different solubility of the different functional layers in the catalyst layer, the dissolution and dispersion effect after mixing and dispersing them was poor, especially the dissolution and dispersion of the stereochemical resin, resulting in a low conductivity. In addition, the anti-reverse electrode layer and the anti-free radical layer were not in the right position, resulting in poor chemical stability of the membrane electrode.
[0220] In Comparative Example 6, no imidazole functional groups were introduced into the graphene oxide in the catalyst slurry and membrane material. This is because the addition of graphene increases the inorganic content of the membrane, leading to an increase in resistance and a decrease in the membrane conductivity. In addition, the arylpyridines were not quaternized, resulting in very few adsorption sites for protons and OH- on the polymer, which seriously affected the proton conductivity and OH- conduction capacity.
[0221] The ionic conductivity of the membrane was tested, and the results are shown in the table below. The results show that after impregnation with acids and alkalis, both proton conductivity and OH- conductivity were formed. The membrane with imidazole-modified graphene oxide exhibited high conductivity, and due to its multilayer structure, the membrane showed high mechanical strength.
[0222] Table 1. Conductivity and tensile strength of the membrane
[0223]
[0224]
[0225] Table 2. Conductivity and tensile strength of the membrane
[0226]
[0227] The dual-effect membrane electrodes prepared in the embodiments and comparative examples of this invention were immersed in Fenton's reagent for durability testing, and the results are shown in the table below. The membranes without multilayer modification and containing ether linkages exhibited significantly poorer chemical resistance.
[0228] Table 3. Test of residual mass of membrane electrode.
[0229] Example 1 99.15 Example 2 99.4 Example 3 98.3 Comparative Example 1 50.3 Comparative Example 2 50.1 Comparative Example 3 49.8 Comparative Example 4 33 Comparative Example 5 45 Comparative Example 6 23
[0230] The dual-effect membrane electrodes prepared in the embodiments and comparative examples of this invention were weighed after adsorbing acids and alkalis, and then immersed in pure water for a certain period of time to test the residual mass rate, thus detecting their ability to retain acids and alkalis. The conductivity retention rate before and after immersion was also tested, and the results are shown in the table below. The conductivity retention rate was poor for the electrode without multilayer modification, while the membrane with imidazole-modified graphene oxide exhibited high conductivity and good conductivity stability.
[0231] Table 4. Acid and alkali absorption capacity, acid and alkali retention capacity, and conductivity retention rate of dual-effect film electrodes.
[0232]
[0233] As shown in Table 5, the dual-effect membrane electrode designed in this invention exhibits better current density under the same voltage during water electrolysis, with current densities exceeding 2000 mA / cm² at an electrolysis voltage of 2.0V. In contrast, the comparative examples show lower performance due to the lack of corresponding methods and structures.
[0234] Table 5 Electrolytic Current Density of Membrane Electrode
[0235]
[0236]
[0237] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A method for preparing a dual-effect membrane electrode for water electrolysis and fuel cells, characterized in that, Includes the following steps: (1) Anode catalyst slurry 1, anode catalyst slurry 2, and anode catalyst slurry 3 are sequentially coated on one side of the double-effect exchange membrane; after drying, cathode catalyst slurry 4, cathode catalyst slurry 5, and cathode catalyst slurry 6 are sequentially coated on the other side of the double-effect exchange membrane, and after drying, a spare double-effect membrane electrode is formed. (2) The prepared standby dual-effect membrane electrode is soaked in an alkaline solution and dried to obtain an anion exchange membrane electrode; the prepared standby dual-effect membrane electrode is soaked in an acidic solution and dried to obtain a proton exchange membrane electrode. The dual-effect exchange membrane comprises quaternized arylpyridine polymer and imidazole-functionalized graphene oxide; The quaternized arylpyridine polymer is obtained by an affinity substitution reaction between an arylpyridine polymer and a haloalkane. The imidazole-functionalized graphene oxide is obtained by attaching an imidazole group to the carboxyl group on graphene oxide. The anode catalyst slurry 1 is prepared by thoroughly mixing catalyst 1, compound 1, quaternized arylpyridine polymer 1, imidazole functionalized graphene oxide 1, and alcohol diluent. Catalyst 1 is 10-70 wt% Pt / C and one or a combination of Pt black. Compound 1 is one or more of microcrystalline cellulose, PVDF, and PTFE. The anode catalyst slurry 2 is prepared by thoroughly mixing catalyst 2, compound 2, quaternized arylpyridine polymer 2, imidazole functionalized graphene oxide 2, and an alcohol diluent. Catalyst 2 is 10-70 wt% Pt / C or one or a combination of two of Pt black. Compound 2 is one or a combination of Ru, Ir, Co, Ni, Ta, Re, Sn, Sb or their oxides. The anode catalyst slurry 3 is prepared by thoroughly mixing catalyst 3, compound 3, quaternized arylpyridine polymer 3, imidazole functionalized graphene oxide 3, and alcohol diluent. Catalyst 3 is 10-70 wt% Pt / C and one or a combination of Pt black. Compound 3 is one or a combination of one or more of TiO2, MnO, MnO2, CeO2, and ZrO2. The cathode catalyst slurry 4 is prepared by thoroughly mixing catalyst 4, compound 4, quaternized arylpyridine polymer 4, imidazole functionalized graphene oxide 4, and alcohol diluent. Catalyst 4 is one or a combination of two of iridium black, iridium oxide, 10-70wt% Pt / C, and Pt black. Compound 4 is one or a combination of microcrystalline cellulose, PVDF, and PTFE. The cathode catalyst slurry 5 is prepared by thoroughly mixing catalyst 5, compound 5, quaternized arylpyridine polymer 5, imidazole functionalized graphene oxide 5, and an alcohol diluent; catalyst 5 is one or a combination of two of iridium black, iridium oxide, amorphous IrOx / Ru catalyst, 10-70wt% Pt / C, and Pt black; compound 5 is one or a combination of one or more of Ru, Ir, Co, Ni, Ta, Re, Sn, Sb, or their oxides. The cathode catalyst slurry 6 is prepared by thoroughly mixing catalyst 6, compound 6, quaternized arylpyridine polymer 6, imidazole functionalized graphene oxide 6, and alcohol diluent. Catalyst 6 is one or a combination of two of the following: iridium black, iridium oxide, amorphous IrOx / Ru catalyst, 10-70wt% Pt / C, and Pt black. Compound 6 is one or a combination of one or more of TiO2, MnO, MnO2, CeO2, and ZrO2.
2. The method for preparing a dual-effect film electrode according to claim 1, characterized in that, The method utilizes a roll-to-roll coating production line, including a conveyor route for transporting the roll material. Along the conveying direction of the conveyor route, the production line sequentially includes a roll unwinding roller, an anode coating zone, a cathode coating zone, an alkaline immersion tank, an acid immersion tank, a main drying oven, and a finished product take-up roller. Along the conveying direction of the conveyor route, the anode coating zone sequentially includes a first anode coating zone, a second anode coating zone, and a third anode spraying zone. The cathode coating zone sequentially includes a first cathode coating zone, a second cathode coating zone, and a third cathode spraying zone. The first anode coating area, the second anode coating area, and the third anode spraying area are respectively equipped with a first heating platform, a second heating platform, and a third heating platform for the coil material. The first cathode coating area, the second cathode coating area, and the third cathode spraying area are each equipped with a first partition drying tunnel, a second partition drying tunnel, and a third partition drying tunnel for the coil material. The first anode coating area, the second anode coating area, the third anode spraying area, the first cathode coating area, the second cathode coating area, and the third cathode spraying area are respectively connected to six feeding systems.
3. The method for preparing a dual-effect film electrode according to claim 2, characterized in that, The preparation method for using a roll-to-roll coating production line includes the following steps: (1) The anode catalyst slurry 1 is placed in a feeding system connected to the first anode coating zone; The anode catalyst slurry 2 is placed in a feeding system that is connected to the second anode coating area; The anode catalyst slurry 3 is placed in a feeding system that is connected to the third anode spraying zone; (2) The cathode catalyst slurry 4 is placed in a feeding system that is connected to the first cathode coating area; The cathode catalyst slurry 5 is placed in a feeding system that is connected to the second cathode coating area; The cathode catalyst slurry 6 is placed in a feeding system that is connected to the third cathode spraying zone; (3) After the dual-effect film is formed into a roll, it is stretched, wound, and installed on the conveyor route of the production line; (4) Along the conveying direction of the double-effect exchange membrane, anodic catalyst slurry 1, anodic catalyst slurry 2, and anodic catalyst slurry 3 are sequentially coated on one side of the double-effect exchange membrane. At the same time as coating, the first heating platform, the second heating platform, and the third heating platform are heated simultaneously. Then, cathode catalyst slurry 4, cathode catalyst slurry 5, and cathode catalyst slurry 6 are sequentially coated on the other side of the double-effect exchange membrane. At the same time as coating, the first zone drying tunnel, the second zone drying tunnel, and the third zone drying tunnel are heated simultaneously to form a spare double-effect membrane electrode. (5) The prepared standby double-effect membrane electrode continues to be conveyed on the roll-to-roll coating production line. After being immersed in the alkaline solution soaking tank and dried in the general oven, it is wound on the finished product winding roller to form an anion exchange membrane electrode. In this state, the acid solution soaking tank is closed. Alternatively, the prepared standby dual-effect membrane electrode continues to be conveyed on the roll-to-roll coating production line. After online immersion in the acid soaking tank and drying in the general oven, it is wound up on the finished product winding roller to form a proton exchange membrane electrode. In this state, the alkaline soaking tank is closed. (6) Offline soaking: The obtained anion exchange membrane electrode is cut into the required size and soaked offline in an alkaline soaking tank. Finally, it is dried to obtain the finished anion exchange membrane electrode in the dual-effect membrane electrode; or the obtained proton exchange membrane electrode is cut into the required size and soaked offline in an acid soaking tank. Finally, it is dried to obtain the finished proton exchange membrane electrode in the dual-effect membrane electrode.
4. The method according to claim 1 or 3, characterized in that, In the anode catalyst slurry 1, the catalyst loading is 0.01-0.1 mg / cm³. 2 The content of catalyst 1 in alcohol dilution solvent is 0.01-20 mg / mL; the mass ratio of catalyst 1, compound 1, quaternized arylpyridine polymer 1, and imidazole functionalized graphene oxide 1 is 1:(5-20):(5-10):(0.01-0.5). In the anode catalyst slurry 2, the catalyst loading is 0.1-0.5 mg / cm³. 2 The content of catalyst 2 in alcohol dilution solvent is 0.1-30 mg / mL; the mass ratio of catalyst 2, compound 2, quaternized arylpyridine polymer 2, and imidazole functionalized graphene oxide 2 is 1:(0.1-3):(2-8):(0.2-5). In the anode catalyst slurry 3, the catalyst loading is 0.1-1.5 mg / cm³. 2 The content of catalyst 3 in alcohol-based diluents is 1-40 mg / mL; the mass ratio of catalyst 3, compound 3, quaternized arylpyridine polymer 3, and imidazole-functionalized graphene oxide 3 is 1:(5-20):(5-10):(0.1-0.5). In the cathode catalyst slurry 4, the catalyst loading is 0.05-0.5 mg / cm³. 2 The content of catalyst 4 in alcohol-based diluents is 0.01-40 mg / mL; the mass ratio of catalyst 4, compound 4, quaternized arylpyridine polymer 4, and imidazole-functionalized graphene oxide 4 is 1:(5-20):(5-10):(0.01-0.5). In the cathode catalyst slurry 5, the catalyst loading is 0.2-1.5 mg / cm³. 2 The content of catalyst 5 in alcohol dilution solvent is 0.1-50 mg / mL; the mass ratio of catalyst 5, compound 5, quaternized arylpyridine polymer 5, and imidazole functionalized graphene oxide 5 is 1:(0.1-5):(2-10):(0.2-10). In the cathode catalyst slurry 6, the catalyst loading is 0.1-3 mg / cm³. 2 The content of catalyst 6 in alcohol-based diluents is 1-80 mg / mL; the mass ratio of catalyst 6, compound 6, quaternized arylpyridine polymer 6, and imidazole-functionalized graphene oxide 6 is 1:(5-20):(5-15):(0.1-2). The alcohol diluents are all mixtures of deionized water and alcohol solvents, with a mass ratio of deionized water to alcohol of 1:0.1-20. The alcohols are one or more of ethanol, ethylene glycol, propanol, and isopropanol.
5. The method according to claim 1 or 3, characterized in that, The preparation method of the dual-effect exchange membrane is as follows: A. Preparation of quaternized arylpyridine polymers: A-1. Add 4-acetylpyridine and aryl hydrocarbons to dichloromethane solvent, add catalyst and protonating agent at low temperature, then return to room temperature, react for one time and then purify to obtain arylpyridine polymer; The molar ratio of 4-acetylpyridine to aryl hydrocarbon is (1:1) to (1.6:1). The molar ratio of the arylpyridine polymer to the haloalkane is (1:1) to (1:5). The aryl hydrocarbon is present in dichloromethane at a concentration of 0.1-2 mol / L; The molar ratio of 4-acetylpyridine to the catalyst is (1:5) to (1:10). The molar ratio of 4-acetylpyridine to the protonating agent is (1:5) to (1:20). The catalyst is selected from trifluoroacetic acid and trichloroacetic acid, and the protonating agent is selected from trifluoromethanesulfonic acid and trinitrobenzenesulfonic acid; The low temperature is -20 to 5°C; The reaction time is 2-72 hours. The aryl hydrocarbon is selected from any one or more of the following structures: ; A-2. Dissolve the arylpyridine polymer from step A-1 in a high-boiling-point solvent, add a haloalkane and heat, react for two hours and then purify to obtain the quaternized arylpyridine polymer. The high-boiling-point solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone; The halogenated hydrocarbon is selected from one or more of iodomethane, bromoethane, bromobutane, and bromohexane; the heating temperature is 50-200℃; The second reaction time is 2-100 hours; The arylpyridine polymer has a concentration of 0.01-2 mol / L in a high-boiling-point solvent; B. Synthesis of imidazole-functionalized graphene oxide: Graphene oxide is heated and refluxed in an acylation reagent until the carboxyl group is completely converted to acyl chloride. After purification, acylated graphene oxide is obtained. Then, it is mixed with a solvent and an imidazole salt with an amino side chain and heated to react. Finally, after purification, the imidazole functionalized graphene oxide is obtained, which is to attach an imidazole group to the carboxyl group on the graphene oxide. The acylation reagent is selected from thionyl chloride and oxalyl chloride; The solvent is selected from one or more of tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide; The mass ratio of the graphene oxide to the volume ratio of the acylation reagent is (1:10)-(1:50) g / ml; The molar ratio of the acylated graphene oxide to the imidazole salt with amino groups on the side chain is (1:1) to (1:3). The mass ratio of the acylated graphene oxide to the volume ratio of the solvent is (1:5)-(1:100) g / ml; The heating temperature of the reflux heating is 70-100℃; The reaction time for the heating reflux is 24-72 hours; The heating temperature for the heating reaction is 60-130℃; The reaction time for the heating reaction is 8-50 hours; The imidazole salt with an amino group on its side chain is one of the following S1-S5 structures: C. Dissolve the quaternized arylpyridine polymer from step A) in a high-boiling-point solvent to form solution one. Disperse the imidazole-functionalized graphene oxide from step B) in a high-boiling-point solvent to form solution two. Mix solution one and solution two again to form a film-forming slurry. Cast the film-forming slurry into a film and dry it to obtain a dual-effect exchange membrane. The high-boiling-point solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone; The mass-to-volume ratio of the quaternized arylpyridine polymer to the high-boiling solvent is (1:5)-(1:100) g / ml; The mass-to-volume ratio of the imidazole-functionalized graphene oxide to the high-boiling-point solvent is (1:20)-(1:200) g / ml; The mass ratio of imidazole-functionalized graphene oxide to quaternized arylpyridine polymer is (1:1000) to (1:10). The wet thickness of the dual-effect exchange membrane is 40-350 μm; The drying process employs vacuum drying, with a vacuum drying temperature of 50-200℃.
6. The preparation method according to claim 3, characterized in that: In step 4), the coating parameters for the anode catalyst slurry 1 are: coating thickness of 1-200 μm, coating speed of 1-10 m / min, and temperature of the first heating platform of 50-150℃; the coating parameters for the anode catalyst slurry 2 are: coating thickness of 1-150 μm, coating speed of 1-20 m / min, and temperature of the second heating platform of 40-120℃; the spraying parameters for the anode catalyst slurry 3 are: spraying thickness of 1-30 μm, spraying speed of 1-15 m / min, and temperature of the third heating platform of 60-180℃. The coating thickness of cathode catalyst slurry 4 is 1-30 μm, the coating speed is 1-10 m / min, and the temperature of the first zone drying tunnel is 70-150℃; the coating parameters of cathode catalyst slurry 5 are: coating thickness 1-50 μm, coating speed 1-10 m / min, and the temperature of the second zone drying tunnel is 60-120℃; the spraying parameters of cathode catalyst slurry 6 are: spraying thickness 0.1-35 μm, spraying speed 1-10 m / min, wet thickness 1-30 μm, and the temperature of the third zone drying tunnel is 80-250℃.
7. The preparation method according to claim 3, characterized in that: The alkaline solution in step (5) is selected from one or more of NaOH, Na2CO3, NaHCO3, KOH, K2CO3, and KHCO3 solutions; the acid in the acidic solution is selected from one or more of sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, polyphosphoric acid, phosphotungstic acid, phosphomolybdic acid, silicotungstic acid, and silicotungstic acid. The concentration of the alkaline solution is 0.1-10 mol / L; The concentration of the acidic solution is 0.01-5 mol / L; The soaking time is 12-100 hours; The drying temperature is 25-80℃; The drying temperature during online impregnation is 60-250℃.
8. A dual-effect membrane electrode for water electrolysis and fuel cells, characterized in that, It is prepared by any one of the preparation methods of claims 1 to 7.
9. The application of the dual-effect film electrode according to claim 8, characterized in that: The dual-effect membrane electrode is used as a membrane electrode in water electrolysis and fuel cells, or applied in anhydrous systems and high-temperature proton exchange membrane fuel cells with an operating temperature of 120-200 ℃.
Citation Information
Patent Citations
Double-effect membrane electrode for water electrolysis and fuel cell and preparation method of double-effect membrane electrode
CN117334971A